Correlation method of measurements of sound power in the near field conditions - CZARNECKI, Stefan; ENGEL, Zbigniew; PANUSZKA, Ryszard (Archives of Acoustics, 1976)
The results of sound power measurements under near field conditions have been compared with the results obtained for far field conditions. For near field measurements correlation and phase methods were used. Far field conditions were investigated by means of reverberation and free-field methods. The experiments were performed on a piston in an infinite baffle, the situation assumed in the calculations. Quite good agreement of the results was obtained at low frequencies. For the higher frequencies this agreement appeared to be worse although this disagreement has been explained theoretically. The usefulness f a correlation method for the measurement of sound power under near field conditions was confirmed. The method can be used in practice for the evaluation of the sound power generated by different parts of machinery.